INFRARED SPECTROSCOPIC ANALYSIS OF COMPLEXATION BETWEEN 5-AMINO ISO-PHTHALIC ACID, COBALT NITRATE, AND ETHYLENEDIAMINE (Journal of Universal Science Research, 2024)
This study investigates the complexation process between 5-amino iso-phthalic acid (IPA), cobalt nitrate, and ethylenediamine (EDA) using Fourier-transform infrared (FTIR) spectroscopy. The observed vibrational shifts in the spectrum provide evidence of functional group coordination and the formation of a stable metal-ligand complex. The results demonstrate changes in the vibrational frequencies of carboxylate, amino, and cobalt-related bonds, confirming structural modifications during the interaction.